COBIT 2019 and ITIL v4 : Moving Away or Closer? - Myint, Su Yee (2024)
This research study will explore the relationship between these well-known IT Management frameworks (COBIT and ITIL) and analyze the latest versions of these two frameworks in the context of IT Governance and Service Management. This research begins by discovering the evolutional developments and reviewing the key principles of each framework. Then it goes through a comparative analysis, observing the core components, processes, and practices of COBIT 2019 and ITIL v4. After that, the study will proceed with both primary data and secondary data analysis for this research work to achieve the research goal which is to observe COBIT and ITIL frameworks are getting convergent or not in their latest versions. Analysis results from the secondary analysis and the findings from the awareness level of IT professionals (respondents of the primary data collection process) will be discussed and the study will be demonstrated their correspondence with its research questions highlighting whether those findings of this research work did really fulfill the research objective or not eventually.